TiO2-Activated Carbon Elaeis Guineensis Jacq Composite Degraded COD and BOD at Batua Raya Waterways - Rasyid, Firnanelty; Chadijah, Sitti; Windasari, Windasari (Chimica et Natura Acta, 2024)
Activated carbon is an important material for purification, adsorbent and catalyst in the chemical industry. This research has been carried out to determine the photocatalytic activity of the modified catalyst and adsorbent TiO2-activated carbon for reduce of COD and BOD of canal water. Carbon composite was successfully synthesized with mixture of two materials that have different physical and chemical properties. Modification TiO2 with porous material was carried out to determine the optimum mass and contact time for reduce COD and BOD in waterways using photocatalysis method. Activated carbon have made from oil palm bunches through the carbonization process. The composite was tested the optimum TiO2-activated carbon with a ratio of 2:0.4 g which was applied into canal water for 60 minutes. The result showed that COD value was 99.65% and BOD 94.44%. The result of SEM data image showed that activated carbon blocked TiO2 clotting and spread on activated carbon. So that TiO2-activated carbon composite can be used to reduce of COD and BOD level in waterways